Pengaruh Penggunaan Mind Mapping Dalam Model Problem Based Learning Terhadap Pencapaian Kompetensi Fisika Peserta Didik Kelas X SMAN 2 Padang Pada Materi Kerja Dan Momentum - Gusmita Cahnia Putri; Letmi Dwiridal; Ramli Ramli (PILLAR OF PHYSICS EDUCATION, 2018)
Physics has complex lesson content so the learning process that will be used must be effective, easy to understand, and make student actively participate. The purpose of this  research is to investigate the effect of using Mind Mapping in the Problem Based Learning (PBL) model on the achievement of students' physic competence at grade 10th SMAN 2 Padang. This type of research is Quasi Experimental Research with Posttest-Only Control Group Design. Population of the research is students at grade 10th SMAN 2 Padang in 2017/2018.  Sampling  technique that use  is purposive sampling. The experiment class using Mind mapping in the PBL  model, and the control class only uses the PBL model. Students' competencies are attitudes, knowledge, and skills. The average of attitude competency in the experimental class is 91.23 higher than the control class of 89.19. The average value of knowledge competence in the experimental class is 72.26 higher than the control class of 66.58. The average value of skill competencies for the experimental class is 90.40 higher than the control class of 86.47. So, it can be concluded that there is an effect which means the use of Mind Mapping in the Problem Based Learning model of the achievement of students' physical competence at grade 10th SMAN 2 Padang.Keywords : Mind Mapping, Problem Based Learning Model, Competence